A fully integrated microchip system for automated forensic short tandem repeat analysis. Issue 11 (17th May 2017) - Han, Junping; Gan, Wupeng; Zhuang, Bin; Sun, Jing; Zhao, Lei; Ye, Jian; Liu, Yao; Li, Cai-Xia; Liu, Peng
Abstract : An integrated microsystem that combines plastic microchips for DNA extraction and PCR with a glass capillary array electrophoresis chip together in a compact instrument has been developed for automated forensic short tandem repeat (STR) analysis. Abstract : We have successfully developed an integrated microsystem that combines two plastic microchips for DNA extraction and PCR amplification with a glass capillary array electrophoresis chip together in a compact control and detection instrument for automated forensic short tandem repeat (STR) analysis. DNA extraction followed by an " in situ PCR" was conducted in a single reaction chamber of the microchip based on a filter paper-based extraction methodology. PCR products were then mixed with sizing standards by an injection electrode and injected into the electrophoresis chip for four-color confocal fluorescence detection. The entire STR analysis can be completed in about two hours without any human intervention. Since the 15-plex STR system has a more stringent requirement for PCR efficiency, we optimized the structure of the plastic DNA extraction and amplification chip, in which the reaction chamber was formed by sandwiching a hollow structure layer with two blank cover layers, to reduce the adsorption of PCR reagents to the surfaces. In addition, PCR additives, bovine serum albumin, poly(ethylene glycol), and more magnesium chloride were included into the on-chip multiplex STR system. The limit-of-detection study demonstrated that our microsystem was able to produce full 15-plex STR profiles from 3.75 ng standard K562 DNA. Buccal swab and whole blood samples were also successfully typed by our system, validating the feasibility of performing rapid DNA typing in a "sample-in-answer-out" manner for on-site forensic human identification.